Los títeres y su incidencia en el cuidado del medio ambiente del primer año de educación básica de la escuela Francisco Robles del cantón Babahoyo, provincia de los Ríos - Tovar Plaza, Tamara Paula (2016)
In the present investigation it is tried to evidence the influence of the puppets in the care of the environment of the first year of the basic education of the School Francisco Robles of the Babahoyo canton, province of Los Ríos, Investigative work In order to learn to respect something first you have to know, to know, to realize the problem and take action. How are you going to separate the garbage and change detergent if you do not know why they do it in what is going to help with that? That is why always the first step is to take "awareness" of the problem to the solo after the possible solutions and then put them into action. From the linguistic point of view, it must be specified that in Spanish, contrary to what happens in other languages.